2012
DOI: 10.4037/ajcc2012859
|View full text |Cite
|
Sign up to set email alerts
|

Building a Nursing Productivity Measure Based on the Synergy Model: First Steps

Abstract: A closed-book, multiple-choice examination following this article tests your under standing of the following objectives: Objective To generate data necessary to develop a nursing productivity system by using the Synergy Model as a conceptual framework. Methods Nurses from 3 different intensive care units participated. In phase 1, charge nurses in focus groups described patient and family indicators considered when making nursepatient assignments. In phase 2, charge nurse data were used to construct a survey fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Productivity is known as the ratio of outputs to inputs (Finkelman, Kenner, 2013). While, nursing productivity is generally defined as the ratio of patient care hours per patient day to salary and benefit costs paid out to staff by the organization (Kohr et al, 2012). Others see nurse productivity as associated with both efficiency of use of clinical nursing in delivering nursing care and the effectiveness of that care related to its quality and appropriateness (Roussel, 2011).…”
mentioning
confidence: 99%
“…Productivity is known as the ratio of outputs to inputs (Finkelman, Kenner, 2013). While, nursing productivity is generally defined as the ratio of patient care hours per patient day to salary and benefit costs paid out to staff by the organization (Kohr et al, 2012). Others see nurse productivity as associated with both efficiency of use of clinical nursing in delivering nursing care and the effectiveness of that care related to its quality and appropriateness (Roussel, 2011).…”
mentioning
confidence: 99%
“…However, previous studies have identified the type of information required for nurses to evaluate patients, 15 and the information provided in the case studies used in our study may have been insufficient for evaluation by comparison. The resulting difficulty in assessing patient characteristics may have affected the assessment of the nursing competencies required in their treatment.…”
Section: Discussionmentioning
confidence: 87%
“…The Synergy Model for Patient Care has been used in a variety of circumstances and for a variety of purposes. Examples of recent uses include staff development, 19 building a nursing productivity measure, 20 and care of patients with acute coronary syndromes. 21 …”
Section: The Aacn Synergy Model For Patient Carementioning
confidence: 99%